Analysis on the implementation of source code collaboration in academic environment / Alfatuzee Bolot - Bolot, Alfatuzee (2005)
Collaboration can be simply defined as cooperation between two or more party in doing a specific work. For many years, concept of collaborative learning in educational highlights on how learning by group rather than learn individually. In learning computer programming language, collaboration can be used as a concept to enhance the development of source code or software. The collaboration among students and lectures in source code development will give a lot of benefits for all computing educational institution. The objectives of this study is to identify the requirements of Source Code Collaboration(SCC) system and to propose a design guideline and research model for future development to implement Source Code Collaboration in academic environment. There are several methods used for conducting this study including by doing general findings and observation, case studies analysis and comparative study from the existence of real world examples. Therefore, the investigations in this work and the expected result of design guideline and research model from this study intended to define the optimum requirements of SCC and to increase the awareness of collaborative learning among lectures and students to enlarge community activities in a healthy way.